The optimization of a mathematical simulation program to describe the nitrogen removal of the oxidation ditch process. (1st June 2014) - Li, Qingxue; Fang, Xiaojun; Zhang, Cuiping; Xiao, Wei
Abstract : To achieve new emission standards and enhance the denitrification of the oxidation ditch in the Handan West Sewage Treatment Plant, this research used the ASM Bio-P model based on self-made simulation software to study the optimum operation of the denitrification efficiency. The results indicate that:1) the volume of the aerobic zone was increased and the volume ratio between aerobic and anoxic zones was controlled to approximately 3:1; 2) the concentration of the dissolved oxygen (DO) in the aerobic zone was increased and was controlled at 1 mg/L in summer and 3 mg/L in winter; 3) the proper sludge retention time (SRT) was controlled and was maintained at 15 d in summer and 20 d in winter; and 4) the appropriate reflux ratio was controlled to 100% and 50% for summer and winter, respectively. The COD, TN, NH3 -N and TP in the effluent reached the first (B) standard of the Discharge Standard of Pollutants for Municipal Wastewater Treatment Plant (GB18918-2002).